Regulatory Resources and Person’s Life Plans under Uncertainty Conditions during COVID-19 Lockdown in Russia - Nailya G. Kondratyuk; Igor Y. Tsyganov; Irina M. Kolesnikova; Varvara I. Morosanova (RUDN Journal of Psychology and Pedagogics, 2021)
The research considers the problem of regulatory resources of the personal life plans in uncertain and unpredictable situations on the material of the COVID-19 pandemic spread in the world and in Russia. The study was conducted during a lockdown in Russia, in an online format, with the help of the Tilda Publishing block website builder and the Google Forms survey administration software. The study sample included 165 respondents aged 16 to 56 years. The Self-regulation Profile Questionnaire - SRPQM 2020 , The Center for Epidemiologic Studies Depression Scale, CES-D , and the authors questionnaire which includes a number of questions related to personal life plans and professional/educational curriculum were used for diagnose. The study results demonstrated that the higher conscious self-regulation development is associated with the higher person's clarity and understanding of the future plans, the more stable career path (including professional and educational goals), and the less actual depressive symptoms. And vice versa: the low level of the conscious self-regulation development correlates with the difficulties with considering the life plans, the fickleness of professional and educational goals, being affected by external factors, and with the pronounced actual manifestations of depression. The data obtained contribute to the development of ideas about the conscious self-regulation phenomenon and human regulatory resources ensuring stability of the personal life plans in situations of uncertainty and serving as a buffer that softens the impact of external stress factors and neutralizes their possible negative consequences.